Multimodal Rehabilitation Combining -Wide-Focused Li-ESWT- and Behavioral Therapy for Coexisting Underactive Bladder, Mild BPH, and Erectile Dysfunction: A Case Report - Farida Arisanti; Anjar Setiadi; Winge W. Arline; Rinesa Larasati (Rifa'Institute, 2026)
Introduction: Managing coexisting detrusor underactivity (UAB), benign prostatic hyperplasia (BPH), and erectile dysfunction (ED) remains challenging when symptoms persist despite maximal medical therapy. Objective: To evaluate the clinical outcomes of a multimodal neurorehabilitation approach combining -wide-focused low-intensity extracorporeal shockwave therapy- (Li-ESWT), fluid management, and relaxation-focused pelvic floor muscle training in a patient with refractory UAB, mild BPH, and ED. Method: A 66-year-old male with cardiometabolic risk presented with persistent lower urinary tract symptoms and ED despite treatment with Dutasteride/Tamsulosin and Bethanechol. Baseline ultrasound showed mild prostatic enlargement (35.4 g), voided volume of 298 mL, peak flow rate (Qmax) of 21.4 mL/s, and post-void residual (PVR) of 100-150 mL. The patient underwent a 12-week multimodal rehabilitation program. Result and Discussion: PVR decreased from 100–150 mL to 40–50 mL, reducing clean intermittent catheterization (CIC) from 3–4 to 1–2 times daily. Functional voided volume increased to 380 mL, nocturnal dribbling resolved, and Qmax remained non-obstructive at 18.2 mL/s, indicating improved detrusor contractile function and quality of life. Conclusions: Multimodal neurorehabilitation incorporating Li-ESWT, behavioral modification, and pelvic floor training may provide a promising non-invasive treatment for refractory UAB, BPH, and ED